Investigation of dynamic cable-deck interaction in a physical model of a cable-stayed bridge. Part I : modal analysis - Elsa Caetano (2000)
A description of an experimental investigation involving the study of the dynamic interaction between the cables and the deck/towers system in cable-stayed bridges is presented. The work was carried out on a physical model of a cable-stayed bridge (the Jindo Bridge, in South Korea), whose characteristics of stiffness and mass have been conveniently scaled. Standard modal analysis tests were performed using both an electrodynamic shaker and a shaking table, leading to the creation of a high quality data base, characterizing the dynamic behaviour of the bridge. The study shows the existence of a clear dynamic interaction between the cables and the deck/towers system, associated with the appearance of several groups of mode shapes, at closely spaced frequencies, involving different cable movements, but similar configurations of the girder and towers.